Correction: Population genomics in South East Asia captures unexpectedly high carrier frequency for treatable inherited disorders. (December 2018) - Bylstra, Yasmin; Kuan, Jyn; Lim, Weng; Bhalshankar, Jaydutt; Teo, Jing; Davila, Sonia; Teh, Bin; Rozen, Steve; Tan, Ene-Choo; Liew, Wendy; Yeo, Khung; Tan, Patrick; et al.
At the time of publication the author Jyn Ling Kuan did not have a master's degree; this has now been amended to BSc. This has now been corrected in the PDF and HTML versions of the article.